Relationship Between the Mid-Upper Arm Circumference of Pregnant Women and the Birth Length of Newborn Babies. - Yuliyanti, Suryani; Boga Dumasela; Minidian Fasitasari (JURNAL KESMAS DAN GIZI (JKG), 2025)
Birth length has been used as an indicator of infants' nutritional status, reflecting the results of linear fetal growth during pregnancy. Meanwhile, the nutritional status of pregnant women can be assessed using the mid-upper arm circumference (MUAC). In Indonesia, MUAC is primarily utilized to classify chronic energy deficiency (CED) and has not been explored as a predictor of infants' nutritional status based on birth length. This study aims to analyze the relationship between MUAC and birth length. A retrospective cohort study was conducted involving 55 pregnant women aged 20-35 years who attended prenatal check-ups and gave birth between January and December 2018. Data were collected from patient records at the Maternal and Child Health Unit of Pulokulon I Community Health Center in Grobogan Regency in July 2019. Pregnant women with incomplete data, those diagnosed with anemia, and babies born prematurely were excluded from the analysis. Data were analyzed using the Rank-Spearman correlation test with SPSS version 16. The analysis of maternal demographic characteristics revealed that only maternal age had a significant impact on the baby's birth length, with a Pearson correlation test showing p = 0.04. The average maternal mid-upper arm circumference was 26.01 ± 3.45 cm, while the average birth length was 48.76 ± 1.49 cm. The study concluded that there was no significant relationship between maternal mid-upper arm circumference and birth length (p-value = 0.931). Further research is needed across various community health centers, involving a larger sample size and additional maternal variables, to determine the effectiveness of mid-upper arm circumference as an indicator for predicting infants' nutritional status. .